Spatiotemporal Clustering of Seismicity in the Kiskatinaw Seismic Monitoring and Mitigation Area - Khajehdehi, Omid; Eaton, David W.; Davidsen, Jörn (Frontiers in Earth Science, 2022)
Induced seismicity has become a concern for industry and nearby residents. Fluid-induced earthquakes are a side effect of industrial operations such as hydraulic fracturing, where high-pressure fluids are pumped into the earth's crust to increase hydrocarbons flow to a well from petroleum-bearing rock formations. Previous studies on fluid-induced seismicity showed the existence of spatiotemporal clustering and aftershock activity. Here, we study seismic catalogs from the Kiskatinaw Seismic Monitoring and Mitigation Area (KSMMA) to investigate spatiotemporal clustering and determine the aftershock activity due to secondary triggering mechanisms such as static and dynamic stress changes arising from preceding seismic events. Our analysis is based on modern tools from statistical seismology such as the Bi-test and triggering analysis. We find significant aftershock triggering and spatiotemporal clustering across KSMMA, but with large spatial variations which might be indicative of preexisting stresses and fault systems. In particular, the aftershock triggering is characterized by rapidly decaying spatial distributions of aftershocks beyond the mainshock rupture area and by a strong dominance of small but frequent triggers, consistent with what has been observed for hydraulic fracturing and saltwater disposal elsewhere.